Effects of cognitive load during interpretation bias modification on interpretation bias and stress reactivity. (September 2020) - Van Bockstaele, Bram; Clarke, Patrick J.F.; Notebaert, Lies; MacLeod, Colin; Salemink, Elske
Abstract: Background and objectives: Interpretation bias modification can affect stress reactivity, yet results have not been consistent. This inconsistency may be partly due to variability in the degree to which training procedures alter interpretation at a more automatic, rather than strategic, level of processing, and a mismatch in available resources between the training and the stress situation. We tested this possibility by investigating whether imposing a secondary cognitive load during interpretation bias modification would strengthen training-induced effects on both interpretation bias and emotional reactivity. Method: We trained 71 participants in a single session to interpret ambiguity either positively or negatively. Half of our participants did so while performing a cognitively demanding secondary task. We assessed the effects of these different training regimes on interpretation bias and both self-reported and physiological indices of stress reactivity. Results: Positive and negative interpretation bias modification resulted in training-congruent changes in interpretation bias. There were no group differences in self-reported stress reactivity, but positive interpretation training did improve recovery from stress as indexed by the heart rate measurement. Countering our hypothesis, the addition of cognitive load during the training increased neither the induced interpretive change nor its emotional impact. Limitations: Sample size was relatively small, though sufficient to detect medium sized effects. Conclusions: Adding cognitive load to interpretation bias modification does not alter training-induced change in interpretation bias or emotional reactivity. Highlights: Interpretation bias modification (IBM) can reduce stress reactivity. We tested whether adding a cognitive load during IBM increases its effectiveness. IBM affected interpretation bias and changes in heart rate following a stressor. Adding cognitive load affected neither interpretive change nor stress reactivity.